The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-69519-5
|View full text |Cite
|
Sign up to set email alerts
|

Coccolithophore community response to ocean acidification and warming in the Eastern Mediterranean Sea: results from a mesocosm experiment

Abstract: Mesocosm experiments have been fundamental to investigate the effects of elevated CO 2 and ocean acidification (OA) on planktic communities. However, few of these experiments have been conducted using naturally nutrient-limited waters and/or considering the combined effects of OA and ocean warming (OW). Coccolithophores are a group of calcifying phytoplankton that can reach high abundances in the Mediterranean Sea, and whose responses to oA are modulated by temperature and nutrients. We present the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 129 publications
(164 reference statements)
0
17
1
Order By: Relevance
“…However, the higher chlorophyll-specific particulate backscattering associated with the nano/micro-phytoplankton population than for the picoplankton, at green and red wavelengths, is not consistent with previous studies (Morel, 1987;Kostadinov et al, 2009). It is possible that some nano-sized phytoplankton groups that have high backscattering efficiencies like coccolithophores, that have been found in the nearby Mediterranean Sea (D'Amario et al, 2020), are present in Red Sea waters. It is also possible that some of the optical environments where larger cells are present in the Red Sea (i.e., near Coral Reefs) include high concentrations of other covarying constituents, such as detritus, bacteria and viruses, that backscatter light with high efficiency (Ahn et al, 1992).…”
Section: Model Parameters In B Bpcontrasting
confidence: 77%
“…However, the higher chlorophyll-specific particulate backscattering associated with the nano/micro-phytoplankton population than for the picoplankton, at green and red wavelengths, is not consistent with previous studies (Morel, 1987;Kostadinov et al, 2009). It is possible that some nano-sized phytoplankton groups that have high backscattering efficiencies like coccolithophores, that have been found in the nearby Mediterranean Sea (D'Amario et al, 2020), are present in Red Sea waters. It is also possible that some of the optical environments where larger cells are present in the Red Sea (i.e., near Coral Reefs) include high concentrations of other covarying constituents, such as detritus, bacteria and viruses, that backscatter light with high efficiency (Ahn et al, 1992).…”
Section: Model Parameters In B Bpcontrasting
confidence: 77%
“…The direct effect of increased temperature and lowered pH on OMZ microeukaryotes is less clear. Acidification will likely decrease the abundance of any calcium test-bearing microeukaryotes in OMZs like it does for coccolithophores (D'Amario et al, 2020). Further, rising temperatures have the potential to increase grazing rates of bacteria by microeukaryotes in oxic waters (Gu et al, 2020;Cabrerizo and Marañón, 2021), but it is unclear whether this can overcome the observed negative effect low oxygen concentrations have on grazing.…”
Section: Response Of Microbes To Climate Change and Continued Deoxygenationmentioning
confidence: 99%
“…The combined impacts of OA and OW have been addressed with contrasting responses, such that the effects of OA and OW are either exacerbated (e.g., Di Santo 2015;D'Amario et al, 2020;Zittier et al 2018;Rodolfo-Metalpa et al, 2011) or ameliorated (e.g., Kroeker et al 2014;Knights et al, 2020;García et al, 2015;Jiang et al, 2018) in the presence of the other stressor (). Meta-analyses have suggested that the combined impacts of OA and OW on species physiology are especially devastating for the larval stages of many species (Przeslawski et al, 2015;Kroeker et al, 2013), presenting a major bottleneck for population persistence under changing oceanic conditions (Przeslawski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%